Modelling Ireland's exchange rates: from EMS to EMU - Derek Bond; Michael J. Harrison; Edward J. O'Brien (European Central Bank (ECB), 2007)
This paper attempts to model the nominal and real exchange rate for Ireland, relative to Germany and the UK from 1975 to 2003. It offers an overview of the theory of purchasing power parity (PPP), focusing particularly on likely sources of nonlinearity. Potential difficulties in placing the analysis in the standard I(1)/I(0) framework are highlighted and comparisons with previous Irish studies are made. Tests for fractional integration and nonlinearity, including random field regressions, are discussed and applied. The results obtained highlight the likely inadequacies of the standard cointegration and STAR approaches to modelling, and point instead to multiple structural changes models. Using this approach, both bilateral nominal exchange rates are effectively modelled, and in the case of Ireland and Germany, PPP is found to be valid not only in the long run, but also in the medium term.
Keywords: C22; C51; F31; F41; 330; fractional Dickey-Fuller tests; multiple structural changes models; purchasing power parity; random field regression; smooth transition autoregression; Wechselkurssystem; Wechselkurs; Kaufkraftparität; Eurozone; Einheitswurzeltest; Irland; Deutschland; Großbritannien